G20 : the Cannes Summit, November 2011 (Newsdesk Communications Ltd LondonGB, 2011)
Includes perspectives under the theme 'A New Way Forward' from selected leaders of the G20, from Lee Myung-bak, President, South Korea; Felipe Calderón, President, Mexico; Recep Tayyip Erdogan, Prime Minister, Republic of Turkey; Susilo Bambang Yudhoyono, President, Indonesia; Barack Obama, President, USA; and Jacob Zuma, President, South. Assesses the past summits. Speaks inter alia, generating global economic growth and jobs; need for financial regulation and supervision, including combating corruption; controlling commodity markets, and climate change.
Keywords: INTERNATIONAL RELATIONS